A Descriptive Study on Perceived Sexual Control in Individuals Who Experience Dating Violence - Amalia, Natasya Putri; Pratiwi, Pradipta Christy; Mahanani, Fatma Kusuma (Developmental and Clinical Psychology, 2023)
Efforts to maintain sexual control over a partner occur in various cases of dating violence. This research examines perceived sexual control from the perspectives of internal sexual control, power-other sexual control, and chance-or-luck sexual control. Descriptive quantitative methods were used in this research. A total of 310 respondents filled out the questionnaire online. The questionnaires used are the Revised Conflict Tactics Scale (CTS2) and MSSCQ, adapted from Snell et al. (1993), which are used to measure internal sexual control, power-other sexual control, and chance-or-luck sexual control. Respondents to this study were 310 people (women = 67%, men = 37%), aged 20–30, who had been or were currently in a relationship for at least one year. The selection of respondents used the purposive sampling method. Data analysis uses descriptive techniques. The research results show that perceived sexual control is generally in the high category. Then internal sexual control, power-other sexual control, and chance-or-luck sexual control are also in the high category.